Designable and dynamic single-walled stiff nanotubes assembled from sequence-defined peptoids - Haibao Jin (Nature Portfolio, 2018)
The application potential of organic nanotubes is currently limited by their lack of designable or dynamic properties. Here, Chen et al. use sequence-defined peptoids to assemble a new family of pH-responsive stiff nanotubes whose dimensions, components and functions can be easily tailored.